HIJABERSMOM COMMUNITY DI PEKANBARU (Studi Tentang Motivasi Bergabung Dalam Kelompok Sosial) - Nofri Yanti Harahap; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to find out the motivation and the hijabersMom community function of member that joined. The kind of research was qualitative descriptive, which is the kind of research to understood the situation to analyze, and to described event that occurred in the society. The data sources were consisted of primary data and the secondary data. The primary data was compiled by doing the interview, while secondary data was compiled by reading the books, internet, and other related document. The sample in this research were 9 people from hijabersmom community Pekanbaru including the coordinator and members. The author has used sample purposive sampling technique. The result of research showed there were two motive of member that join in the hijabersmom community Pekanbaru. At the first was sosiogenesist motive such as to added relation and knowledge, to followed the fashion trends and to be organized. At the second was teogenetist motive such as because of willing to learned more about religious thing. This community has manifest functions for members such as to be place to added the obedience, humanity, creativity and economy. At the second was latent functions from this community such as there was society perception that HijabersMom were community who make a point of style and fashion.Keywords : Community, Motivation, HijabersMom